THE ROLE AND IMPORTANCE OF USING TECHNOLOGY IN TEACHING ENGLISH (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This  article  enlightens  the  role  and  importance  of  using technology in teaching English language.